2007
DOI: 10.1210/me.2006-0519
|View full text |Cite
|
Sign up to set email alerts
|

The Deoxyribonucleic Acid Repair Protein Flap Endonuclease-1 Modulates Estrogen-Responsive Gene Expression

Abstract: The ligand-occupied estrogen receptor alpha (ERalpha) initiates changes in gene expression through its interaction with target DNA. The capacity of ERalpha to modulate gene expression is influenced by the association of the receptor with a variety of coregulatory proteins. To further understand the role of these coregulatory proteins in ERalpha-mediated transcription, we have isolated and identified proteins associated with ERalpha when it is bound to the consensus estrogen response element. One of the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 73 publications
5
40
0
Order By: Relevance
“…A careful examination of RhoGDIa amino acid sequence failed to identify any nuclear localization signal, suggesting that another protein may assist in the shuttling of RhoGDIa between the cytoplasm and the nucleus. It seems plausible that cdc42 isoform1, a RhoGTPase family member with a polybasic region in its C-terminal end that can function as a nuclear localization signal (Lanning et al 2003, Williams 2003, might perform this function since we identified both isoforms 1 and 2 of cdc42 in our agarose gel purification experiments as ERa-associated proteins (Schultz-Norton et al 2007). Alternatively, RhoGDIa could be accompanied by a protein such as 14-3-3, which binds and helps to redistribute an array of signaling proteins (Fu et al 2000, Kino et al 2003, Diviani et al 2004.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…A careful examination of RhoGDIa amino acid sequence failed to identify any nuclear localization signal, suggesting that another protein may assist in the shuttling of RhoGDIa between the cytoplasm and the nucleus. It seems plausible that cdc42 isoform1, a RhoGTPase family member with a polybasic region in its C-terminal end that can function as a nuclear localization signal (Lanning et al 2003, Williams 2003, might perform this function since we identified both isoforms 1 and 2 of cdc42 in our agarose gel purification experiments as ERa-associated proteins (Schultz-Norton et al 2007). Alternatively, RhoGDIa could be accompanied by a protein such as 14-3-3, which binds and helps to redistribute an array of signaling proteins (Fu et al 2000, Kino et al 2003, Diviani et al 2004.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, we were surprised when we identified endogenously expressed RhoGDIa from HeLa nuclear extracts as a component of a large multiprotein complex associated with the DNA-bound ERa (Schultz-Norton et al 2007).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations